Cegah Stunting dengan Pola Makan, Asuh, Hygiene, dan Sanitasi: Prevent Stunting by Diet, Parenting, Hygiene and Sanitation - Noprianty, Richa; Dahliah, Dedeh; Nur’aeni, Siti; Rifai, Susan Irawan; Santoso, Rahmat; Jumiatun, Jumiatun (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Baros is one of the sub-districts in Cimahi, where stunting is relatively high. Data from the Puskesmas Kelurahan Baros Mekar shows that 43 children are indicated to be stunted. The results of interviews with cadres showed that the community needs more knowledge and insight regarding stunting. Apart from that, there needs to be more public awareness regarding the importance of maintaining a balance of nutrients and vitamins in food. Community service was carried out in September 2023 by lecturers and students at Bhakti Kencana University. The target of the activity is families with 30 children aged 0–5 years. Activities include providing education about stunting prevention by lecturers and the nutrition section of the Puskesmas Cigugur Tengah, demonstrations of a nutritional menu balanced with my plate’s contents, and how to breastfeed and wash hands correctly. After that, a stunting screening is carried out. Participants were given pre-test and post-test questionnaires regarding stunting knowledge and filled in data on the child’s weight. The presentation of knowledge about parenting patterns at the pre-test was 77.02%, the post-test was 84.02%, the pre-test hygiene knowledge was 99.52%, and the post-test was 100%, while the pre-test sanitation knowledge was 80.37%, and post-test was 87.77%. The nutritional status of toddlers based on BB/U showed that BB was less than 3.3%, very low BB was 6.7%, normal was 76.7%, and the risk of being overweight was 13.3%. It is hoped that increasing knowledge about stunting can be implemented to support optimal child growth and development.